2013
DOI: 10.1002/hed.23434
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after primary chemoradiotherapy for N3 (>6 cm) head and neck squamous cell carcinoma after an FDG‐PET‐‐guided neck management policy

Abstract: The rate of INF remains low when following a PET-directed neck management policy after definitive CRT for N3 (>6 cm) HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…A recent retrospective analysis by Ranck et al [22] suggested that a post-radiotherapy neck dissection might decrease the incidence of distant failure in patients presenting with advanced nodal disease even if a complete clinical remission is achieved, but further prospective studies are needed to confirm if a subgroup of patients actually benefit from planned neck dissections. Regarding regional control, even patients with extensive neck disease have a low rate of regional recurrence when treated with modern techniques [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective analysis by Ranck et al [22] suggested that a post-radiotherapy neck dissection might decrease the incidence of distant failure in patients presenting with advanced nodal disease even if a complete clinical remission is achieved, but further prospective studies are needed to confirm if a subgroup of patients actually benefit from planned neck dissections. Regarding regional control, even patients with extensive neck disease have a low rate of regional recurrence when treated with modern techniques [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In one of the largest recent nonsurgical series evaluating outcomes for OPSCC, Garden et al found that increasing N stage was associated with worse regional control, with neck recurrence in 17% of N3 patients. Although other recent nonsurgical series have found similar regional recurrence rates, no controlled trial has been performed to compare surgical and nonsurgical treatment modalities for N3 neck disease from HPV‐related OPSCC …”
Section: Discussionmentioning
confidence: 99%
“…One of the most probable explications for this prognostic fluctuation between series with limited size is the rate of patients included with papillomavirus‐related disease. Actually, the rates of oropharyngeal localizations among series of N3 previously published range from 13% to 76%, depending on the country and the period . As expected, a recent analysis of the National Cancer Database for patients having N3 head and neck cancer showed a foreseeable trend towards better survival for patients with oropharyngeal squamous cell carcinoma (OPSCC) .…”
Section: Introductionmentioning
confidence: 80%
“…A few monocentric studies, as well as a recent pool analysis of 2 prospective randomized trials, have been previously published related to this very advanced neck staging that has been historically associated with very poor outcomes and a high rate of distant metastasis . However, the rates of oropharyngeal localizations among series of N3 have been ranging from 13% for Chan et al, to 76% for Adams et al, depending on the country and the date . Results from more recent studies are somehow very divergent regarding treatment outcomes specifically in OPSCC .…”
Section: Discussionmentioning
confidence: 99%